Etiese prediking in post-apartheid Suid-Afrika? Enkele homiletiese oorwegings - Burrows, Shaun; Cilliers, Johan (Stellenbosch Theological Journal, 2018)
Ethical preaching in post-apartheid South Africa? A few homiletic considerations This article will try to indicate that while the church's approach during the apartheid era was characterized by liberation theology and preaching, the post-apartheid era - that is still characterized by social decay, moral impoverishment and especially an increase in poverty, family violence, divorce and a spirit of individualism - asks for an increased focus on sustainable poverty eradication. It is argued that in post-apartheid South Africa a fundamental consensus on binding values, non-negotiable standards and morally acceptable ground attitudes are urgently needed. It is in this context that the role of ethical preaching is examined. In a context of widespread poverty, unemployment and a sense of insecurity, apathy, unconcern and depression among many ethical preaching, as an orientation event, can bring a new dignity to people.